Exploring Muslim Bumiputra entrepreneurs’ reluctances toward halal certification in Malaysia’s hotel and tourism sector - Tumiran, Mohd Amzari; Ruzulan, Zulaipa; Yusof, Kamaru Salam; Jamaludin, Mohammad Aizat (Secholian Publication, 2025)
Halal certification contributes to shaping Malaysia's hotel and tourism industries, particularly by catering to the needs of Muslim travellers and furthering the country's global reputation as a centre of Islamic tourism. However, while Malaysia leads the world in the halal-tourism business, a degree of resistance has been observed among Muslim Bumiputra entrepreneurs toward halal certification in the hotel and tourism industry. This review aims to explore the reluctances of Muslim Bumiputra entrepreneurs toward halal certification in Malaysia’s hotel and tourism sector. A qualitative review analysis was conducted to understand the cultural and behavioural factors influencing this reluctance. The review analysis revealed several Muslim Bumiputra entrepreneurs' reluctances toward halal certification in Malaysia’s hotel and tourism sector, namely: (a) assumption of presumed halal status; (b) limited awareness of certification standards; (c) resource and operational constraints; and (d) lack of perceived market pressure. In conclusion, the reluctance of Muslim Bumiputra entrepreneurs in Malaysia’s hotel and tourism sector to pursue halal certification is driven by interrelated factors such as presumed halal status, limited awareness of certification standards, operational and resource limitations, and low perceived market pressure. Future studies should focus on evaluating the effectiveness of targeted education campaigns and financial incentives.